Implementation of Qur'anic Learning Management in The General Community - Harahap, Muhammad Sapii; Hasibuan, Muhammad Syarif Muda; Karo, Tiy Kusmarrabbi; Intan Nuraini Mendrofa (As-sunnah: Jurnal Pengabdian Masyarakat, 2026)
This community service article reports on the implementation of Quranic learning management for the general community through a Thematic Community Service Programme (KKNT) conducted by students of the Sekolah Tinggi Agama Islam (STAI) As-Sunnah, Deli Serdang, North Sumatra, in collaboration with the community of Muara Lembu Village, Singingi Sub-district, Kuantan Singingi Regency, Riau Province, from 3 to 18 March 2025. The programme involved child learners aged 5 to 14 years, utilising the Community Based Research (CBR) method with a participatory action research framework. The objectives were: to inspire learners to love the Quran; to establish Quranic recitation improvement groups (tahsin); and to form memorisation groups (tahfiz) for seven selected surahs of Juz 30. Following two structured cycles of learning, approximately 95 per cent of learners successfully memorised seven surahs — Al-Dhuha (93), Al-Tin (95), Al-ʿAlaq (96), Al-Qadr (97), Al-Bayyinah (98), Al-Zalzalah (99), and Al-ʿAdiyat (100) — and demonstrated correct recitation in accordance with the rules of tajwid. The findings affirm that a structured, motivation-centred learning management approach, grounded in Islamic educational principles and community collaboration, yields measurable outcomes in Quranic literacy at the grassroots level.